2002
DOI: 10.1200/jco.2002.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Timing of Pulmonary Metastases Identification on Prognosis of Patients With Osteosarcoma: The Japanese Musculoskeletal Oncology Group Study

Abstract: Time of identification of lung metastasis is an important prognostic factor. In terms of clinical behavior, groups 2 and 3 are completely different than group 4. These data ensure the need to stratify stage III osteosarcomas into subgroups according to the time of diagnosis of lung metastases. To improve the survival of osteosarcoma patients, new treatment modalities should be introduced into the treatment armamentarium for lung metastasis from osteosarcoma, especially in groups 1, 2, and 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
103
3
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(111 citation statements)
references
References 33 publications
(22 reference statements)
3
103
3
2
Order By: Relevance
“…In two more recent series, a benefit for second-line chemotherapy was not demonstrated. Tsuchiya et al 25 reported similar overall survival for patients with pulmonary recurrence treated with surgery alone or with second-line chemotherapy and surgery.Ferrari et al 26 reported no difference in overall survival between patients treated with or without second-line chemotherapy after first disease recurrence-.For patients with completely excised isolated pulmonary recurrence, there was no difference in second event-free survival with the addition of chemotherapy. A subgroup analysis of patients with completely excised isolated pulmonary recurrence showed a superior 5-year survival with surgery alone compared with surgery and second-line chemotherapy.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In two more recent series, a benefit for second-line chemotherapy was not demonstrated. Tsuchiya et al 25 reported similar overall survival for patients with pulmonary recurrence treated with surgery alone or with second-line chemotherapy and surgery.Ferrari et al 26 reported no difference in overall survival between patients treated with or without second-line chemotherapy after first disease recurrence-.For patients with completely excised isolated pulmonary recurrence, there was no difference in second event-free survival with the addition of chemotherapy. A subgroup analysis of patients with completely excised isolated pulmonary recurrence showed a superior 5-year survival with surgery alone compared with surgery and second-line chemotherapy.…”
Section: Discussionmentioning
confidence: 91%
“…Inability to achieve CR2 has been associated with an exceptionally poor outcome, with overall survival rates ranging from 0% to 8%. 8,9,11,13,19,20,25,26 Goorin et al 12 reported a survival rate of 32% (7 of 22 patients) among patients with unresectable recurrent OS, although the duration of follow-up was not reported. Improved survival has also been associated with prolonged RFI, variably de- fined as longer than 6 months, 9 longer than 8 months, 16 and longer than 24 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 5-year survival rate after the detection of lung metastasis is less than 30%. 14 Despite recent improvements in chemotherapy and surgery, the current strategies for the treatment of high-grade OS do not improve significantly the outcome for the patient.…”
mentioning
confidence: 99%